Conversion of residential housing to kindergarten in perspective to the local authority requirement / Nurul ‘Aiin Shahari - Shahari, Nurul ‘Aiin (Faculty of Architecture, Planning and Surveying, 2008)
Preschool education is the foundation of the children education, which can influence their future growth and development In order to provide good preschool education, a preschool education center or kindergarten should be provided effectively. Nevertheless, the planning and provisions of the kindergarten in the new housing schemes are not effective. It may generate many problems such us, insufficient in number and unplanned location, overcrowding of children, insufficient space and lack of playing equipments within the kindergarten. To get a clear picture of issue and problems related to kindergarten, a study has been carried out at three different locations which are in Rawang, Shah Alam and Kuala Lumpur. The locations are selected it has varieties of land uses and kindergartens issue on unplanned kindergartens. The study involves five stages consisting of preliminary study, theoretical study, information gathering, analysis and finding and solutions. Preliminary study is carried out to give a clear picture of the topic. Then, theoretical study, which involves the requirement and planning standards of kindergarten at the residential housing and the background of preschool education, has been carried out.